CONSERVATIVE TREATMENT OF LOWER URINARY TRACT DYSFUNCTION - Anamarija Meglič; Matjaž Kopač (The Society for Children with Metabolic Disorders, 2023)
Lower urinary tract dysfunction, closely related to bowel dysfunction, means functional abnormalities of the bladder and urethra. Different types of lower urinary tract dysfunction are divided according to symptoms or according to the cause. Treatment is directed to the cause. Neurogenic lower urinary tract dysfunction can cause irreversible damage to the upper urinary tract and changes in the bladder wall long before the clinical picture manifests as urinary leakage. Therefore, it is essential to diagnose the neurogenic defect with the resulting lower urinary tract dysfunction as soon as possible after birth and to treat the condition proactively. The standard therapy for neurogenic lower urinary tract dysfunction is clean intermittent catheterization in combination with an anticholinergic. Non-neurogenic lower urinary tract dysfunction, resulting in sudden, unexpected urge to void, urgency, leakage of urine, sphincter-detrusor dyssynergy and other forms, is often associated with a deterioration in the quality of life and negatively affects the child's self-esteem. The child develops different behavioural patterns to delay urination or stop the urgency. With anamnestic data, a diary and a clinical picture, we can easily define the diagnosis and start as soon as possible with non-pharmacological measures, standard and various types of special urotherapy.